Perioperative Interventions to Minimize Blood Loss at the Time of Hysterectomy for Uterine Leiomyomas: A Systematic Review and Meta-analysis. Issue 3 (March 2020) - Gingold, Julian A.; Chichura, Anna; Harnegie, Mary Pat; Kho, Rosanne M.
Abstract : (Abstracted from J Minim Invasive Gynecol 2019;26:1234–1252) Almost 70% of white and more than 80% of black premenopausal women are affected by uterine leiomyomas. Medical or conservative procedures can manage many leiomyoma-related symptoms.